Barium-based scintillating MOFs for X-ray dosage detection with intrinsic energy resolution via luminescent multidentate naphthalene disulfonate moieties. Issue 17 (7th April 2021) - Lu, Jian; Gao, Juan; Wang, Wen-Fei; Li, Bao-Yi; Li, Pei-Xin; Zheng, Fa-Kun; Guo, Guo-Cong
Abstract : Non-toxic Ba-SMOFs assembled by luminescent multidentate naphthalene-sulfonate moieties exhibit merited intrinsic energy resolution for X-ray dosage detection. Abstract : Luminescent multidentate naphthalene-sulfonic moieties and non-toxic barium ions worked synergistically to fabricate scintillating barium-based metal–organic frameworks into latent applications of X-ray dosage detection with their merited intrinsic energy resolution.